Association of physical performance with cognitive impairment in middle-aged to older haemodialysis patients: a multicentre cross-sectional observational study - Xu, Jia; Zhao, Xinhui; Guo, Qi; Yu, Cheng; Ding, Wei; Niu, Jianying; Zhao, Junli; Zhang, Liming; Zhang, Suhua; Qi, Hualin; Xi, Minhui (Journal of international medical research, 2024)
Objective To determine the prevalence of cognitive impairment (CI) among middle-aged to older patients receiving maintenance haemodialysis (MHD) and to investigate the potential association between CI and physical performance. Methods This cross-sectional observational study enrolled participants aged 55–85 years who received MHD. Cognitive status was assessed using the Mini Mental State Examination (MMSE). Physical performance was measured by hand grip strength, the Timed Up and Go Test (TUGT) and the 4-m walking speed. Sociodemographic, clinical and laboratory parameters were recorded for each patient. Results The study included 592 patients (363 males); and of these, 126 (21.3%) were diagnosed with CI. Compared with patients with normal cognitive function, those with CI were significantly older and had significantly longer dialysis duration, lower educational level, higher Malnutrition Inflammation Score, higher depression and higher Charlson Comorbidity Index score. After adjustment for covariates, multiple regression analysis suggested that grip strength (odds ratio [OR] = 0.959, 95% confidence interval [CI] = 0.924, 0.996) and 4-m walking speed (OR = 0.161, 95% CI = 0.070, 0.368) were protective factors. TUGT (OR = 1.037, 95%CI = 1.003, 1.071) was a risk factor. Conclusion Physical performance was correlated with CI and might be a significant indicator for the early identification of CI in middle-aged to older MHD patients.